The Effect Of Motivation And Leadership Styles Of Lecturer Professions On Organizational Commitment - Suryawan, Ian Nurpatria (Jurnal Manajemen, 2018)
This research is intended to test influence Motivation and Leadership Style against Organizational Commitment work lecturer at Universities in Jakarta. The Universities is a private university located in Jakarta, Indonesia. The sample used purposive sampling technique, who works as a lecturer at the Universities. Instrument analysis of data used is multiple regression analysis by the aid Partial Least Square (PLS) program. Based on the results of the study found that there is a positive relationship. The result is Motivation and Leadership Style against Job Satisfaction, Motivation and Leadership Style against Job Performance, Motivation and Leadership Style against Organizational Commitment.